Current Updates of Biomaterials for Skin Replacement: A Systematic Review - Normalina Sandora; Nur Amalina Fitria; Aditya Wardhana; Nandita Melati Putri; Akhmad Noviandi Syarif; Tyas Rahmah Kusuma; Benati Karimah (Jurnal Plastik Rekonstruksi, 2025)
Background: The human skin envelops the entire body surface and is highly susceptible to damage. Partial- and full-thickness skin loss often necessitates the use of skin substitutes. Autologous grafting remains the gold standard for skin replacement. Furthermore, the application is usually constrained by the limited availability of donor skin, the technical challenges of surgery, and the added difficulties encountered in severe cases. In this systematic review, we summarise the strengths and limitations of biological and synthetic biomaterials as skin substitutes, with evidence drawn from clinical practice, human trials, and preclinical animal studies. This systematic review evaluates the advantages and disadvantages of biological and synthetic biomaterials used as skin substitutes, drawing evidence from clinical practice, human studies, and animal studies.”Method: We performed a comprehensive literature review using the search engines OVID, ScienceDirect, Google Scholar, and PubMed databases. Search terms or keywords included "artificial skin," "biomaterials," "skin substitute," "full-thickness burn," "synthetic materials," "burn graft materials," and "wound care." From an initial pool of 97 articles, 65 met the inclusion criteria, which required peer-reviewed studies published in English after 2000, focusing on biomaterials for skin substitutes evaluated in clinical, human, or animal studies.Results:  Skin substitutes commercially available in the market were predominantly incorporated with human fibroblasts and keratinocytes within a three-dimensional matrix, with a preference for biological materials due to their biocompatibility. Nevertheless, biological substitutes face challenges such as limited availability, extended production time, high costs, and lack of immediate usability. In contrast, synthetic substitutes are more accessible and scalable but often do not integrate well with the recipient's tissue, which limits their clinical efficacy.Conclusion: While both biological and synthetic artificial skin substitutes are available on the market, none of the current options fully meet the ideal criteria for skin replacement, such as affordability, availability, seamless integration with the surrounding tissue, and the ability to minimise scarring. More research is needed to address these limitations and advance the development of next-generation biomaterials that can effectively replace skin.